(untitled) (Revista de Artes Marciales Asiáticas, 2025)
The Brazilian folklorist historiography has traditionally used the example of the Paraguayan War to call for the martial character of capoeira. According to these authors, this art was not only used in combat but may also have been decisive in certain battles. This paper aims to establish the current state of affairs in this regard, as well as provide new sources and ideas that may validate or refute these statements, given their significant role in the construction of Brazil’s national historical narrative. This article will first analyse the presence of capoeira fighters in the Paraguayan War, with particular emphasis on the case of the Zouaves, the soldier Marcolino, and the specialists in naval boarding combat. Thereafter, the study seeks to determine the extent to which capoeira could have been transferable to the military context at that time.